2021
DOI: 10.2188/jea.je20200625
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Change and COVID-19 in Japan: Mobile Data Analysis of Locations of Infection

Abstract: Background: As the COVID-19 pandemic spread, the Japanese government declared a state of emergency on April 7, 2020 for seven prefectures, and on April 16, 2020 for all prefectures. The Japanese Prime Minister and governors requested people to adopt self-restraint behaviors, including working from home and refraining from visiting nightlife spots. However, the effectiveness of the mobility change due to such requests in reducing the spread of COVID-19 has been little investigated. The present study examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 10 publications
10
54
0
Order By: Relevance
“…The exposure-response relationships of population mobilities and meteorological factors with R t are consistent with previous works [17, 24, 25]. For example, the residual and workplace mobility change were not slightly related to the fluctuation of R t while the recreation mobility change was significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The exposure-response relationships of population mobilities and meteorological factors with R t are consistent with previous works [17, 24, 25]. For example, the residual and workplace mobility change were not slightly related to the fluctuation of R t while the recreation mobility change was significant.…”
Section: Discussionsupporting
confidence: 90%
“…For example, the residual and workplace mobility change were not slightly related to the fluctuation of while the recreation mobility change was significant. This relationship in Tokyo were reported in the previous study [17]. The exposure-response outcome of solar radiation indicated a significant negative correlation while that of wind speed shows a significant positive correlation (Supplementary Table S1), and similar relationships have been reported elsewhere [24,25].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Arimura et al demonstrated that the declaration reduced human mobility by up to nearly 90% in Sapporo City (Hokkaido Prefecture), depending on the place and time frame of a day [ 20 ]. Nagata et al, who tracked human mobility in Tokyo, Osaka, and Aichi Prefectures using smartphone data, pointed out that the reduction in human mobility started before the first declaration of the state of emergency, and that the degree of reduction varied from place to place [ 21 ]. Furthermore, Kajitani et al found that a 20–35% reduction in mobility may have been necessary to hold back the pandemic (i.e., to reduce the effective reproduction number to one or less) in the situation during the first wave of the pandemic in the business and commercial districts of nine prefectures including Tokyo [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Rt value >1 indicates that the number of cases is increasing, whereas an Rt of <1 suggests that the infection spread is slowing. Prediction of Rt has been extensively studied using human mobility data to forecast the number of future cases and to develop an effective strategy for public health measures [ 7 , 8 ]. There are also other studies that used machine learning techniques or biological data for the prediction of Rt [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%